Radix Rehmanniae and Corni Fructus against Diabetic Nephropathy via AGE-RAGE Signaling Pathway. (2nd December 2020) - Chen, Jing; Chen, Yuping; Shu, Anmei; Lu, Jinfu; Du, Qiu; Yang, Yuwei; Lv, Zhiyang; Xu, Huiqin
Abstract : Background and Aims . Radix Rehmanniae and Corni Fructus (RC) have been widely applied to treat diabetic nephropathy (DN) for centuries. But the mechanism of how RC plays the therapeutic role against DN is unclear as yet. Methods . The information about RC was obtained from a public database. The active compounds of RC were screened by oral bioavailability (OB) and drug-likeness (DL). Gene ontology (GO) analysis was performed to realize the key targets of RC, and an active compound-potential target network was created. The therapeutic effects of RC active compounds and their key signal pathways were preliminarily probed via network pharmacology analysis and animal experiments. Results . In this study, 29 active compounds from RC and 64 key targets related to DN were collected using the network pharmacology method. The pathway enrichment analysis showed that RC regulated advanced glycosylation end product (AGE-) RAGE and IL-17 signaling pathways to treat DN. The animal experiments revealed that RC significantly improved metabolic parameters, inflammation renal structure, and function to protect the kidney against DN. Conclusions . The results revealed the relationship between multicomponents and multitargets of RC. The administratiom of RC might remit the DM-induced renal damage through the AGE-RAGE signaling pathway to improve metabolic parameters and protect renal structure and function.